1999
DOI: 10.1046/j.1365-2915.1999.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of five species of the Anopheles dirus complex from Thailand, using allele‐specific polymerase chain reaction

Abstract: The Anopheles dirus complex of mosquitoes contains some of the most important vectors of malaria in Southeast Asia. To distinguish five species of the complex that occur in Thailand, a method using the polymerase chain reaction (PCR) was developed. The method utilizes allele-specific amplification to detect fixed differences between the species in the DNA sequence of the ribosomal DNA internal transcribed spacer 2. Primers were designed to amplify fragments of diagnostic length from the DNA of the different sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
172
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(173 citation statements)
references
References 18 publications
0
172
1
Order By: Relevance
“…An. cracens from all localities was subjected for molecular analysis based on inter-transcribed spacer region 2 (ITS2) of ribosomal DNA [11]- [13] in order to confirm the species. Figure 3 showed that those mosquitoes were confirmed as An.…”
Section: Anopheles Nemophilousmentioning
confidence: 99%
“…An. cracens from all localities was subjected for molecular analysis based on inter-transcribed spacer region 2 (ITS2) of ribosomal DNA [11]- [13] in order to confirm the species. Figure 3 showed that those mosquitoes were confirmed as An.…”
Section: Anopheles Nemophilousmentioning
confidence: 99%
“…Anopheles mosquitoes were morphologically sorted by taxon before using specific AS-PCR assays for species identification within the complex or the group [20][21][22]. Each individual was split in two pieces, head-thorax for species identification and abdomen for midgut bacteria analysis.…”
Section: Mosquito Collections and Species Identificationmentioning
confidence: 99%
“…In Southeast Asia, Anopheles vectors belong to species complexes with different involvement in the transmission of pathogens [19]. Few sibling species of the Dirus and Minimus Complexes and the Maculatus Group are involved in malaria and BLF, but specific role of each sibling species and factors influencing this role have never been studied due to the lack of reliable methods for species identification, now available [20][21][22]. As mosquito microbiota is one of the factors influencing pathogen transmission, this chapter is presenting the biodiversity of bacteria in the midgut of field-collected adults of 10 Anopheles species, topic less studied compared to the large number of studies presenting bacteria in the defense against parasites in laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…dirus B, which is one of the important malaria vectors, has been studied in many areas, for example, molecular studies of insect glutathione S-transferases 26,27,32,33,34 , genetic studies of Anopheles species complexes 2,13,49,50,51 , and malaria transmission 6,9,19,39,42 . However, little is known about the salivary gland proteins of this mosquito species.…”
Section: Introductionmentioning
confidence: 99%